2005
DOI: 10.1002/chin.200538167
|View full text |Cite
|
Sign up to set email alerts
|

N‐Arylpiperazine‐1‐carboxamide Derivatives: A Novel Series of Orally Active Nonsteroidal Androgen Receptor Antagonists.

Abstract: Antagonists. -To improve the in vivo antiandrogenic activity of the parent of compounds (V), which is a more potent in vitro AR antagonist than bicalutamide, the parent is modified by conversion of the piperazine ring into alternative cyclic amines, ring expansion, introduction of an alkyl group onto the piperazine ring, and by varying the substitution pattern of the phenyl ring. Trans-dimethylpiperazine derivatives (V) are potent AR antagonists. Within this series, (Vd) shows the most potent antiandrogenic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…We have previously reported a new series of arylpiperazine derivatives as potent nonsteroidal AR antagonists. 34,35 Among these, compound 5 showed more potent activity than bicalutamide (4), both in vitro and in vivo in the testosterone propionatetreated castrated rat model. However, 5 exhibited little activity in the mature intact rat model, which might be a more suitable model to reflect the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported a new series of arylpiperazine derivatives as potent nonsteroidal AR antagonists. 34,35 Among these, compound 5 showed more potent activity than bicalutamide (4), both in vitro and in vivo in the testosterone propionatetreated castrated rat model. However, 5 exhibited little activity in the mature intact rat model, which might be a more suitable model to reflect the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the AR antagonists that have been discovered thus far have been developed through ligand-based drug design, which relies on the pharmacophores of known drugs. Because of the characteristics of ligand-based design, most AR antagonists seem to contain the same basic scaffolds as the known drugs, such as bicalutamide and flutamide or other non-steroidal AR agonists (32,33). As an example, MDV3100, now in phase III clinical trials, was developed from the non-steroidal AR agonist RU59063 by modifying the chemical structures systemically while maintaining the key chemical scaffold (34).…”
mentioning
confidence: 99%
“…The aryl substituents at N 1 -position were 3-chlorophenyl, 3-(trifluoromethyl)phenyl, 4-fluorophenyl, 2-pyridyl, and 2-pyrimidyl, while the aryl group at N 4 -position was either nitro substituted or nitro and trifluoromethyl disubstituted. A broad analysis of the structure -activity relationship indicated that a 4-nitrophenyl (9,10,12,14,16,18) or a 4-nitrobenzyl (29)(30)(31)(32) group at N 4 -position of piperazines generally resulted in potent activity. Addition of a carbonyl linker (20-28) imparted better activity, and addition of a methylene linker (29-32) reduced activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, arylpiperazine derivatives have been reported as potent nonsteroidal AR antagonists, 31,32 and some of them † CDRI Communication No. 7892.…”
Section: Introductionmentioning
confidence: 99%